PC-based real-time control system - Peiris Jeganathan Terrance. (2008)
This report provides detailed information on the design of a microprocessor based real-time control system and how the control parameters can be set and monitored through a PC. The project can be divided into two main sections: 1) Real-time control system 2) Real-time monitoring and editing.